Volodarsk apatite deposit in the east Pryasovia region - Datsenko, Liudmyla; Даценко, Людмила Миколаївна; Даценко, Людмила Николаевна; Movchan, Serhii; Мовчан, Сергій Іванович; Мовчан, Сергей Иванович; Maliuta, Serhii; Малюта, Сергій Іванович; Малюта, Сергей Иванович; Chebanova, Yuliia; Чебанова, Юлія Василівна; Чебанова, Юлия Васильевна; et al. (My University, 2020)
Volodarsk deposit of complex ilmenite-magnetite-apatite ores is located within the ore field of the Kalchytsk ore district of the same name. Foundin the process of GSM-200, studied in the process of search and evaluation work.
Keywords: apatites; Volodarsk site; archaea; proterozoic; Demyanivsk (Sachkinsk) world